Social support and community embeddedness protect against post-disaster depression among immigrants: a Vietnamese American case study - Pham, NhuNgoc K.; Do, Mai; Diep, Jannette (Frontiers in Psychiatry, 2023)
Immigrants often face increased vulnerabilities to disaster-related poor health and recovery, compared to mainstream populations. Little is known about Hurricane Harvey’s impacts among the storm affected area’s large Vietnamese American population. Our study documented diverse psychological experiences and recovery challenges one-year post-storm among a sample of 120 Vietnamese Americans residing in the Houston, Texas area. Using linear regression modeling, we examined the association between social support and depressive symptom development among these storm-affected Vietnamese Americans. Social support encapsulating both social embeddedness and perceived support was measured by the Louisville Social Support Scale and depressive symptom development was measured by 18 items that assessed emotional distress. These items included loss of appetite, loss of concentration, exposure to persistent pain, and the exhibition of hopelessness, tiredness, sadness, frustration, discouragement, desperation, exhaustion, disgraced, anger, and craziness. We found adverse post-disaster health outcomes, as well as potential avenues to mitigate them, that should be taken into consideration in the design and implementation of inclusive disaster programs. A high level of social support lowered depressive symptomology among Vietnamese Americans post-Hurricane Harvey, even when accounting for Hurricane Harvey-related home damages and injuries/illness. The negative association between social support and depressive symptom development remained after accounting for both post-storm self-rated mental and physical health. Our results suggested that public health practitioners and emergency management entities should prioritize social support resources to foster mental well-being after hurricanes among Vietnamese Americans as future hurricanes are expected to be stronger and more prevalent along the United States Gulf Coast.